Heterotropic pregnancy following induction of ovulation with clomiphene - Jogi, Sangeeta Raman; Babbar, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Hetrotopic pregnancy is a rare entity with a difficult preoperative diagnosis and potentially dangerous outcome. A case of 36 years old G3P2 had received Clomiphen Citrate for three cycles for ovulation induction presented with amenorrhea for two months with severe pain in abdomen and bleeding. She was diagnosed as a case of right ectopic with 8 weeks of intrauterine pregnancy.